1992
DOI: 10.1159/000175771
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Evaluation of Left Ventricular Function and Correlation with Autonomic Cardiac Neuropathy in Diabetic Patients

Abstract: Left ventricular function of 20 diabetic patients was investigated at rest and during hand-grip test using radionuclide ventriculography. The aim of the study was to discuss the correlation of cardiac function with autonomic cardiac neuropathy (ACN) in diabetic subjects. ACN was tested using heart rate response to valsalva maneuver, standing up, deep breathing; blood pressure response to standing up, sustained hand-grip, and additionally corrected QT(QTc) measurements. Plasma glucose regulation was screened wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The present study also shows an inverse correlation between neuropathy and longitudinal myocardial diastolic function. The sympathetic overactivity [27] and increase in resting work product in these patients [28] may be directly related to functional compensation. Possibly, the change in autonomic function and myocardial innervation is responsible for compensated increased radial function in diabetic patients with preserved global ejection fraction.…”
Section: Changes In Longitudinal and Radial Functionmentioning
confidence: 93%
“…The present study also shows an inverse correlation between neuropathy and longitudinal myocardial diastolic function. The sympathetic overactivity [27] and increase in resting work product in these patients [28] may be directly related to functional compensation. Possibly, the change in autonomic function and myocardial innervation is responsible for compensated increased radial function in diabetic patients with preserved global ejection fraction.…”
Section: Changes In Longitudinal and Radial Functionmentioning
confidence: 93%
“…However, echocardiography and radionucleotide scanning have shown that the isovolumic relaxation time and left ventricular diastolic filling time are prolonged in asymptomatic diabetic patients with cardiac denervation (32,33), indicating that some or all of these changes could be due to cardiac denervation. Support for this theory can be found in studies of diabetic children and young adults in which no evidence of diabetic cardiomyopathy was found when diabetes was not accompanied by cardiac denervation, hypertension, or ischemic heart disease (34)(35)(36)(37).…”
Section: Noninvasive and Invasive Humanmentioning
confidence: 96%
“…We used radionuclide ventriculography (RNV) at rest, which is a reliable method to assess both systolic and diastolic LV function in patients with diabetes (14).…”
mentioning
confidence: 99%